2020
DOI: 10.1159/000510914
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Is a Significant Predictor of Severe Illness in Coronavirus Disease 2019

Abstract: Introduction As red blood cell distribution width (RDW) significantly predicts clinical outcomes in patients with respiratory tract infections and in those with critical illnesses, we performed a critical analysis of the literature to explore the potential prognostic role of this laboratory parameter in coronavirus disease 2019 (COVID-19). Methods An electronic search was conducted in Medline, Scopus and Web of Science, using the keywords “coronavirus disease 2019” OR “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
(47 reference statements)
5
39
0
Order By: Relevance
“…We also found a few hematological indices that may be potential risk factors. High red cell distribution width (RDW) was associated with mortality in our study and was also identified in a recent meta-analysis of three studies as a risk factor 47 . Low lymphocyte percentage was a top-10 risk factor in cohort B, which may be related to immune functioning and response to infections.…”
Section: Discussionsupporting
confidence: 81%
“…We also found a few hematological indices that may be potential risk factors. High red cell distribution width (RDW) was associated with mortality in our study and was also identified in a recent meta-analysis of three studies as a risk factor 47 . Low lymphocyte percentage was a top-10 risk factor in cohort B, which may be related to immune functioning and response to infections.…”
Section: Discussionsupporting
confidence: 81%
“…A systematic review and meta-analysis has previously investigated whether RDW values predict severe disease in patients with SARS-CoV-2 infection [ 48 ]. While the reported weighted mean difference between patients with and without severe disease are comparable with those observed in our study (0.69 vs. 0.56%) only three studies were assessed, including a study published in MedRxiv but not peer reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an electronic search reporting on three studies on the total number of 11,445 COVID-19 patients and 2654 severe patients, RDW-CV was higher in COVID-19 patients with severe illness than in those with mild disease. They revealed that the absolute RDW-CV value was 0.69% higher in severe patients compared with those with mild disease [ 28 ]. A retrospective study has been conducted to investigate the relationship between RDW and COVID-19 mortality risk in 1198 adult patients diagnosed with SARS-CoV-2 at 4 Partners Healthcare Network Hospitals between 4 March 2020, and 28 April 2020.…”
Section: Discussionmentioning
confidence: 99%